Health Communication Strategies in Dengue Fever Prevention at Wonokusumo Health Center Surabaya - Satrio Bagas Prakoso; Moh Agung Kurniawan (Yayasan Citra Dharma Cindekia, 2026)
This study aims to analyze the implementation of health communication strategies as well as the supporting and inhibiting factors affecting communication effectiveness in the Dengue Hemorrhagic Fever (DHF) prevention program at the Wonokusumo Community Health Center (Puskesmas) in Surabaya. This study employs a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, interviews, and documentation involving healthcare workers, health volunteers (kader), and community members participating in the DHF prevention program. The results indicate that the health communication strategy is executed through health counseling,